Can brain games help smokers quit?: Results of a randomized clinical trial. (1st November 2016) - Loughead, James; Falcone, Mary; Wileyto, E. Paul; Albelda, Benjamin; Audrain-McGovern, Janet; Cao, Wen; Kurtz, Matthew M.; Gur, Ruben C.; Lerman, Caryn
Highlights: Nicotine withdrawal produces deficits in cognitive function which impede cessation. Computerized cognitive training has shown promise for enhancing cognitive function. Smokers completed web-based cognitive or control training during smoking cessation. The cognitive training group showed small improvements in cognitive performance. Cognitive training did not improve quit outcomes compared to control. Abstract: Background and aims: Deficits in cognitive function are observed during nicotine withdrawal and present a challenge to successful smoking cessation. This clinical trial evaluated a cognitive exercise training (CT) program to improve smoking cessation rates. Methods: Adult treatment-seeking smokers (n = 213) were randomized to receive nicotine patch therapy and 12 weeks of either computerized CT or computerized relaxation (control) training. Smoking status was biochemically verified at the end of treatment and 6-month follow-up. Results: Quit rates did not differ by treatment arm at either time-point, nor were there effects on withdrawal symptoms or smoking urges. Reaction time for emotion recognition and verbal interference tasks showed improvement in the CT group. When including only successful quitters, improvements in recognition memory, verbal interference accuracy, and attention switching error rate were also observed in the CT group, while commission errors on the continuous performance task decreased in the control group. Conclusions: Despite modest changes in cognitive performance, these results do not support the efficacy of computerized cognitive training as an adjunctive therapy for smoking cessation.